The silent boy - Lowry, Lois. (New York : Dell Laurel-Leaf, 2005)
Young Katy Thatcher, the daughter of the town doctor, becomes friends with Jacob, a teenager who is "touched in the head," which allows her to understand what really happened when the unwanted infant of Jacob's sister is found dead.
"Readers circle"--Cover.
Library Media Connection starred.
School Library Journal.
Wilson's Junior High School.
6.9
5-8
Keywords: Babies -- Fiction; Brothers and sisters -- Fiction; People with mental disabilities -- Fiction; Unmarried mothers -- Fiction; Infants -- Fiction; Mentally handicapped -- Fiction; Siblings -- Fiction; Unmarried mothers -- Fiction